PERAN DAN STRATEGI PENGEMBANGAN WISATA AIR TERJUN KEBO AMUK (TEDUNAN) DALAM MENINGKATKAN EKONOMI MASYARAKAT DESA SITILUHUR KECAMATAN GEMBONG KABUPATEN PATI - Faiz Aminuddin; Abdul Mutholib (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2018)
PERAN DAN STRATEGI PENGEMBANGAN WISATA AIR TERJUN KEBO AMUK (TEDUNAN) DALAM MENINGKATKAN EKONOMI MASYARAKAT DESA SITILUHUR KECAMATAN GEMBONG KABUPATEN PATI Faiz Aminuddin Dosen Institut Pesantren Mathali’ul Falah Pati Email: fifa-iz@yahoo.com Abdul Mutholib Peneliti Wisata Air Terjun Kebo Amuk Sitiluhur Email: abdulmutholib@gmail.com Abstract The role and tourism development strategy waterfall Kebo Amuk (Tedunan) in improving the economy villagers Sitiluhur in Gembong Pati. Skripsi. Pati: the faculty dakwah and community development institute Mathali’ul Falah 2017. Indonesia country is a that has the potential resources abounding, biodiversity and that which remained history and culture natural resources will be economic growth when recources it can be in governance well consistent with what most attractive to the community so the utilization of natural resources it will not spend time or matter due to the failure to shift in managing a resources. As is the case in a waterfall Kebo Amuk in the villagers Sitiluhur in Gembong Pati. Research aims to understand the role in the development of a waterfall kebo amuk in the development of economic the village community sitiluhur, conducted by looking at, how the role and strategy in development tourist destinations a waterfall kebo amuk (Tedunan of community economy improvement, whatever the factors that appear in the development of tourism a waterfall kebo amuk (Tedunan), how impacts viewed from development tourist destinations a waterfall kebo amuk (Tedunan). The research is a fieldwork adopting descriptive .A method of data collection was carried out by interviews, observation, and documentation .Analysis done with analysis qualitative milles and huberman through a process data collection, data reduction, data display, verification data. In which the validity of the data using a technique trianggulasi good interview, observation, and documentation .As for the findings in thesis this is a village that has the potential natural have not yet been widely exumated and development as in waterfall Kebo Amuk (Tedunan). The process of development a waterfall Kebo Amuk be conducted by way of planning, the implementation, of the evaluation. As for the goal is to improve on the community economy. A method which is executed is to optimize the use of these roles with from stakeholders. The evaluation is done as a whole ranging from cognitive aspect of, effective, psychomotor. Stage of the proceeding the development of a waterfall Kebo Amuk done with planning, the implementation of the, evaluation.